A Critical Discourse Analysis of the Zimbabwean Education Amendment Act, 2019 - Ndlovu, Eventhough; Bowa, Makomborero Allen (Journal for Studies in Humanities and Social Sciences, 2023)
In 2013, Zimbabwe adopted the Constitution of Zimbabwe Amendment (No.20) Act. This Constitution has dedicated Sections 6 and 63 which regulate language use, and in the absence of a written language policy, the two Sections serve as the de facto language policy. The inclusion of the two Sections is a major milestone in the history of language planning, policy, and management in Zimbabwe, especially given that the previous Constitution was completely silent on language issues. In 2019 the Ministry of Primary and Secondary Education adopted the Education Amendment Act, 2019 in order to align the Act with the Constitution. Against this background, this article provides a Critical Discourse Analysis of this Act in order to examine the adequacy or lack thereof of its language provisions. The study employed a multi-method approach to data collection in order to ensure triangulation of results. The main source of data was document analysis of the Act and other related policy frameworks to determine the adequacy or lack thereof of its language provisions. This was complemented by semi-structured interviews and focus group discussions with purposively sampled key participants in the education sector. Findings of this study show that the Act does not mark a departure from the past trilingual language-ineducation policy. In covert, overt, and subtle ways, the Act reproduces, maintains, perpetuates, entrenches and sustains the hegemony of English, Shona and Ndebele.